Influence of dispersion slope on soliton spectral tunneling in photonic crystal fiber - Yang, Yunxia; Yang, Hua; Tong, Xiongfeng; Zhao, Saili; Chen, Shuyuan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
We report a numerical investigation of how the dispersion slope affects the soliton spectral tunneling (SST) in a photonic crystal fiber with three zero dispersion wavelengths. It is discovered that a larger dispersion slope makes group-velocity mismatch between the initial soliton and the transferred wave thereby suppressing the SST effect, while a proper decrease of the dispersion slope enhances the SST effect to widen a supercontinuum range. Besides, we find a soliton-like leaking dispersion wave, which can sustain information and energy for a short time within a particular spectral range.
Optica Applicata, Vol. 51, 2021, nr 3, s. 415-427
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; soliton spectral tunneling; supercontinuum generation; dispersion slope